Understanding Group and Leader (UGL) trainers' personality characteristics and affective profiles - Rapp Ricciardi, Max; Åkerman, Jeanette; Eerikäinen, Peter; Ambjörnsson, Annika; Andersson Arntén, Ann-Christine; Mihailovic, Marko; Archer, Trevor; Garcia, Danilo (Frontiers in Psychology, 2014)
Background: The Development of Groups and Leaders (UGL), provided by the Swedish National Defence College and mentored by UGL-trainers, is one of the most popular management programs among civilians in Sweden. However, there is a lack of scientific evidence regarding the training. We used the affective profile model (i.e., the combination of positive, PA, and negative affect, NA) to mapp important markers of empowerment, self-awareness, adaptive coping skills, and maturity among the UGL-trainers. The aims were: (1) to compare profiles between UGL-trainers and managers/supervisors and (2) to investigate differences in personal characteristics. Method: UGL-trainers (N = 153) and the comparison group (104 Swedish Chiefs of Police) completed an online survey on optimism, self-esteem, locus of control, and affect. The four profiles are: self-fulfilling (high PA, low NA), high affective (high PA, high NA), low affective (high PA, low NA), and self-destructive (low PA, high NA), Results: The self-fulfilling profile was more common among UGL-trainers (25.70%) than among Chiefs of Police (19.20%). UGL-trainers, compared to Chiefs of Police, were more likely to express a self-fulling than a low affective profile (OR=2.22, p < .05) and a high affective than a low affective profile (OR=1.43, p <.001). UGL-trainers with a self-fulfilling profile, compared to those with a self-destructive profile, scored higher in optimism, higher in self-esteem, and lower in external locus of control. Conclusions: The probability of self-fulfilment rather than low affectivity was higher among UGL-trainers. Self-fulfilment was associated to markers of self-awareness and adaptive coping skills. However, the most common profile was the low affective, which is associated to low performance during stress, low degree of personal development, low degree of purpose in life, and low resilience. Hence, it might be important for UGL-trainers to have a continuos training in awareness after certification.